The Longitudinal Effects of Non-injection Substance Use on Sustained HIV Viral Load Undetectability Among MSM and Heterosexual Men in Brazil and Thailand: The Role of ART Adherence and Depressive Symptoms (HPTN 063) - Kiyomi Tsuyuki (2019)
© 2019, Springer Science+Business Media, LLC, part of Springer Nature. The effect of non-injection substance use on HIV viral load (VL) is understudied in international settings. Data are from HPTN063, a longitudinal observational study of HIV-infected individuals in Brazil, Thailand, and Zambia, with focus on men with VL data (Brazil = 146; Thailand = 159). Generalized linear mixed models (GLMM) assessed whether non-injection substance use (stimulants, cannabis, alcohol, polysubstance) was associated with VL undetectability. ART adherence and depressive symptoms were examined as mediators of the association. In Thailand, substance use was not significantly associated with VL undetectability or ART adherence, but alcohol misuse among MSM was associated with increased odds of depression (AOR = 2.75; 95% CI 1.20, 6.32, p = 0.02). In Brazil, alcohol misuse by MSM was associated with decreased odds of undetectable VL (AOR = 0.34; 95% CI 0.13, 0.92, p = 0.03). Polysubstance use by heterosexual men in Brazil was associated with decreased odds of ART adherence (AOR = 0.25; 95% CI 0.08, 0.78, p = 0.02). VL suppression appears attainable among non-injection substance users. Substance use interventions among HIV-positive men should address depression, adherence, and VL undetectability.